Strategi Pemanfaatan Bantuan Corporate Social Responsibility Dalam Mencegah Konflik Petani Dengan Satwa Dilindungi Di Gampong Paya Baro Kabupaten Aceh Barat - Yolanda, Yolanda; Sardini, Rahman; Alamsyah, Fitrah; Edem, Edem; Sopar, Sopar (UNIVERSITAS SERAMBI MEKKAH, 2025)
Agriculture in Indonesia is a vital sector that absorbs around 28.21% of the workforce and contributes 13.57% to GDP in the third quarter of 2023. Agriculture in Gampong Paya Baro faces challenges with the introduction of animals into rice fields due to deforestation. This study aims to explain the strategy of using CSR funds to improve the economy of farmers and how the community prevents conflicts with these animals. The method used by the researcher is qualitative. Gampong Paya Baro Agriculture has several CSR programs including the provision of seeds and fertilizers, irrigation, water pumps, and rice threshers. While the way the community prevents animals from entering the settlement is by lighting torches, firecrackers, building fences, and calling professional handlers.